The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/nu12010009
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of α-Linolenic Acid on Non-Alcoholic Hepatic Steatosis and Interleukin-6 and -10 in Wistar Rats

Abstract: Consumption of omega-3 (n-3) polyunsaturated fatty acids (PUFA) is related to improvement in the inflammatory response associated with decreases in metabolic disorders of obesity, such as low-grade inflammation and hepatic steatosis. Linseed (Linum usitatissimum) oil is a primary source of n-3 fatty acids (FAs) of plant origin, particularly α-linolenic acid, and provides an alternative for the ingestion of n-3 PUFA by persons allergic to, or wishing to avoid, animal sources. In our study, we evaluated the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 55 publications
(78 reference statements)
3
15
0
Order By: Relevance
“…Similar results we observed in adipose tissue weight (Table 4), the group supplemented with olive oil plus C. brasiliense oil had lower weight of the principal visceral fats, including epididymal adipose tissue; in mice, this is one of the main deposit areas of visceral fat [50]. Other relevant sites, such as mesenteric and retroperitoneal fat [51], also diminished compared with the control group. This effect can be associated with the presence of tocopherols and mainly of tocotrienols that are present in both C. brasiliense oil, as demonstrated in our study, and olive oil [52].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Similar results we observed in adipose tissue weight (Table 4), the group supplemented with olive oil plus C. brasiliense oil had lower weight of the principal visceral fats, including epididymal adipose tissue; in mice, this is one of the main deposit areas of visceral fat [50]. Other relevant sites, such as mesenteric and retroperitoneal fat [51], also diminished compared with the control group. This effect can be associated with the presence of tocopherols and mainly of tocotrienols that are present in both C. brasiliense oil, as demonstrated in our study, and olive oil [52].…”
Section: Resultssupporting
confidence: 85%
“…However, a build-up of free FAs occurred in the liver, except group OO + CO that showed only microvesicular steatosis, demonstrating that the synergic effect of the mix of olive oil with C. brasiliense oil may have played a slight protective role, due to a higher concentration of antioxidants. These are known for beneficial action in biological systems and protection against oxidative damages [54] as the oxidative stress is one of the causes of hepatocellular lesions [51]. [55] reported that the administration of C. brasiliense oil at 400 mg/kg in mice induced with diethylnitrosamine 10 µg/g reduced the development of preneoplastic lesions and hepatic adenoma.…”
Section: Resultsmentioning
confidence: 99%
“…However, MAFLD is commonly linked with hyperleptinemia alongside declines in hepatic LEPR, suggesting the development of resistance against leptin anti‐lipogenic actions 12,13 . Consequently, sustained abnormal hepatic lipid metabolism provokes extensive oxidative stress 14,15 and chronic inflammation 16,17 followed by tissue damage, apoptosis, and progressive declines in liver functions 3,18 …”
Section: Introductionmentioning
confidence: 99%
“…An increase in physical activity should also be recommended. It is likely that there will not be only one right approach for all patients with NAFLD, it will be necessary to adapt the diet individually, including the inclusion of n-3 fatty acids, foods with higher monounsaturated fatty acids, fruits, vegetables and reducing the intake of saturated fats or simple carbohydrates ( 6 , 7 ). Recently, it was proposed that food intake regulating peptides play a significant role in obesity regulation and may have the potential to be a drug for obesity treatment ( 8 11 ).…”
Section: Introductionmentioning
confidence: 99%